Impact of spontaneous abortion history and induced abortion history on perinatal outcomes of singleton pregnancies - Hanxiang Sun; Jing Mao; Xiujuan Su; Qiaoling Du (BMC, 2023)
Abstract Background At present, there are several studies on abortion history and perinatal outcomes, but there is no unified conclusion whether the history of abortion and different types of abortion are related to perinatal complications of subsequent pregnancy. We aim to study the impact of different types of abortion history on perinatal outcomes of singleton pregnancies. Methods This was a retrospective study from a maternity and infant hospital in Shanghai, China from 2016 to 2020. Pregnant women who gave birth to live singleton infant were included (n = 75,773). We classified abortion into spontaneous abortion (SAB) and induced abortion (IA). We compared the perinatal outcomes of singleton pregnancies with different abortion histories and used Logistic regression analysis to evaluate the associations between pre-pregnancy abortion history with perinatal outcomes. Results We observed that pregnant women with a history of abortion were more likely to have a premature delivery (0.99% VS 0.45%), gestational diabetes mellitus (GDM) (13.40% VS 10.29%), placenta abnormality (8.16% VS 5.06%), placenta previa (5.65% VS 3.75%), placenta accreta (0.18% VS 0.04%), and placenta adhesion (2.79% VS 1.03%) than those who obtained singleton pregnancies without a history of abortion. When confounding factors were adjusted, differences in placenta abnormality still existed (excluding placenta abruption). The odds ratios and 95% confidence interval of placenta previa, placenta accreta, and placenta adhesion in pregnant women with only SAB history, only IA history, and both abortion history were 1.294(1.174-1.427), 1.272(1.159-1.396), and 1.390(1.188-1.625), 2.688(1.344-5.374), 2.549(1.268-5.125), and 5.041(2.232-11.386), 2.170(1.872-2.515), 2.028(1.738-2.366), and 3.580(2.917-4.395), respectively. Conclusions Our research showed that pregnant women who have a history of abortion before pregnancy were more likely to have premature birth, GDM, placenta previa, placenta accreta, and placenta adhesion. After adjusting for confounding factors, we found that the history of SAB, IA, and both SAB and IA history were related to the increased risk of placenta previa, placenta accreta, and placenta adhesion.